Answer:
12x^2 -21x -6
Step-by-step explanation:
(3x-6)(4x+1)
FOIL
first 3x*4x= 12x^2
outer 3x*1 = 3x
inner -6*4x = -24x
last -6*1 = -6
Add them together
12x^2 +3x -24x -6
Combine like terms
12x^2 -21x -6
Answer:
Step-by-step explanation:
<u>Given function:</u>
<u>Initial population size is when t = 0</u>
- P(0) = 400(1.22)⁰ = 400(1) = 400
<u>The multiple of 1.22 is applied every year, so the ratio of change is:</u>
This is an exponential growth which represents 22% annual growth.
Answer:
4 option D
Step-by-step explanation:
Note that log2(2^n)=n
Thus we have:
Log2(2)+log2(8)=1+log2(2³)=1+3=4
Answer:
1. 3/5
2. 9/20
3. 1/5
4. 9/10
Step-by-step explanation:
Answer:
6.2
Step-by-step explanation:
You can find the median by adding up all of the numbers and dividing the result by how many numbers there are.
add them all together: 5 + 6 +5+6+9 = 31
there are five people, so divided 31 by 5
31 divided by 5 = 6.2
6.2